Vociferando paisagens, bradando nostalgias: a cena musical black metal norueguesa como espaço de (re)significações sobre o mundo natural - Lopes, João Guilherme Santos de Araújo (2021)
The From the beginning of 1990s, the underground music scene related to Heavy Metal was haunted by the appearance of a small blaze that would shine in the skies of the far north of Europe. This blaze that would come to be known for representing the second generation – or wave – of a musicality created even in the 1980s, but which, within Norway, would take on new aspects in the musical, performance and representation spheres: Norwegian Black Metal. In its splendor, the norwegian black metal scene was marked by artistic production based on satanism, misanthropy and death, from the figurative to the pratical sense – involving church arson and murders among its members. Nevertheless, this same scene ends up at a certain momento finding in nature a new exploratory lyrical and imaginary bias, distancing itself from the themes that once existed and leading to a series of discourses that evoke from nostalgia and topophilia and traversing the modern world by fascist-paganism elements. In this sense, the presente work aims to analyze how the norwegian black metal music scence (permeating the 1990s until the 2010s) incorporates in the representations about nature a new locus in its artistic productions, taking into account the memory and the uses of the past of those who make up such a scene. Under the prism of Schama (1996), Tuan (1980) and Assman (2011), we will investigate how artistic production (lyrical and imagery) of that scene conceives its own readings to the natural space and that, over the following decades, end up for influencing other local/regional scenes within black metal music and even outside it. Following this steps, we will focus our research on various media forms such as lp’s, k-7 tapes, cd’s, promotional inserts, posters, shows and promotional flyers, magazines and fanzines.